Caracterização molecular e citogenética de frutos de Caryocar brasiliense (Cambess) com e sem espinho no caroço - Londe, Luciana Nogueira (2010)
CHAPTER II: Pequi, Caryocar brasiliense, is one of the species of highlight at the biome of the Brazilian savannah due to its utilization in culinary, popular medicine, industry in general, and iron and steel industry. It presents an elevated index of exploration, being capable of entering the list of the endangered species. In the region of São José do Xingu (MT), a tree of pequi without thorn at the mesocarp was found and this enables to improve pequi not only for consumption, taking advantage of the high appreciation it already has. To detect the existing genomic differences between the pequi with and without the thorn at the endocarp, RADP markers were utilized. The generated polymorphisms were cloned and sequenced in order to identify the sequences responsible for the fenotypical alteration. It was observed that the pequi without thorn is genetically isolated from the other populations of pequi with thorn at the endocarp, proving that this characteristic is related to the genetic divergence of the species. Analysis in BLASTn evidenced the similarity of the Dof1 genes of Zea mays, in the population with thorn, and in the population without thorn, with the gene of phosphinotricin acetyl transferase of Z. mays. In the analysis of BLASTx, the similarity was verified with the proteins responsible for the deficiency in ferric reductase 4, in the pequi without thorn and catalase, in the pequi without thorn. CHAPTER III:The pequi, Cayocar brasiliense Cambess. Is a feature of Brazilian cerrado plant suffering extractive action, mainly for food. It is a plant very appreciated in the regions of Minas Gerais, especially in the north of this state. In the region of Sao Jose do Xingu, Mato Grosso, was found in a plant which had no thorns in the core and this allowed further research to discover the lack of thorns as it is an unwanted feature of the plant. Thus, the cytogenetic study, using conventional Giemsa staining, NOR, banda C, DAPI and CMA3 were used for comparison between the pequi with and without spines in the putamen. It was found that these differences are not attributed to chromosomal differences between the two types of pequi. Both have the same chromosome number, the marking of NOR, C banding was not verified due to the size of chromosomes and differences in staining with DAPI and CMA3 could not be verified although related to these characteristics. CHAPTER IV: The pequi is a species that is gathered and today is seen as a source for the production of biodiesel. The objective of this study was to identify sequences from a cDNA library that are involved in the metabolic pathways for production of pequi fruit, to gain a better understanding of the species and its biological and genetic properties. To do so, a cDNA library was created and the clones were cloned and sequenced. These identified sequences were deposited in GenBank. Most of the sequences found are associated with protection against oxidative stress in plants, some are transcription factors and others provide structural and pathogenic resistance.